Bridging the educational gaps of health professionals in oncogenomics: results from a pilot e-learning course - Stellacci, Emilia; Martinelli, Simone; Carbone, Pietro; Demuru, Elena; Genuardi, Maurizio; Ghiorzo, Paola; Novelli, Giuseppe; Di Pucchio, Alessandra; Regini, Federica Maria; Guerrera, Debora; Vittozzi, Andrea; Barbina, Donatella; et al. (Frontiers in Medicine, 2024)
Background Genetic and genomic literacy of health professionals is of utmost importance to realize the full potential of personalized medicine. As part of a European Union project, we piloted an e-learning course on oncogenomics, primarily targeted to physicians, and we assessed both its effectiveness and users’ satisfaction. Methods The course materials were developed in English according to the Problem-Based Learning method. Learning objectives, covering the basic principles of genetics and the OMICS technologies applied to oncology, were defined based on previously identified core competencies. We used a pre-test vs. post-test study design to assess knowledge improvements. Performance results by demographic and professional characteristics of participants were analyzed using univariate or multivariate statistical methods. Results Overall, 346 Italian professionals (61% physicians, 39% biologists) successfully completed the course. Their average post-test score was almost 19% higher than the pre-test (71.6% vs. 52.9%), with no significant differences by sex. Older age (>50 years) and southern area of residence were both correlated with higher gains. The average proportion of correct answers in the final certification test after three attempts was 85% (69% at first attempt), with some differences across professional categories. Methodology, quality of content and usability of the e-learning platform were all highly rated via satisfaction questionnaire (average scores between 4 and 5, scale 1 to 5). Conclusion The pilot phase confirmed the suitability of the e-learning as a cost-effective method to improve oncogenomic literacy of health professionals. Translation into natural languages and accreditation by European or country-specific Continuing Medical Education systems will be the main incentives for wider dissemination.